Impact of Resident Involvement in Neurosurgery: An American College of Surgeons’ National Surgical Quality Improvement Program Database Analysis of 33,977 Patients - Andreea Seicean; Prateek Kumar; Sinziana Seicean; Duncan Neuhauser; Warren R. Selman; Nicholas C. Bambakidis (Neurospine, 2018)
Objective There is conflicting and limited literature on the effect of intraoperative resident involvement on surgical outcomes. Our study assessed effects of resident involvement on outcomes in patients undergoing neurosurgery. Methods We identified 33,977 adult neurosurgical cases from 374 hospitals in the 2006–2012 National Surgical Quality Improvement Program, a prospectively collected national database with established reproducibility and validity. Outcomes were compared according to resident involvement before and after 1:1 matching on procedure and perioperative risk factors. Results Resident involvement was documented in 13,654 cases. We matched 10,170 resident-involved cases with 10,170 attending-alone. In the matched sample, resident involvement was associated with increased surgery duration (average, 34 minutes) and slight increases in odds for prolonged hospital stay (odds ratio, 1.2; 95% confidence interval [CI], 1.2–1.3) and complications (odds ratio, 1.2; 95% CI, 1.1–1.3) including infections (odds ratio, 1.4; 95% CI, 1.2–1.7). Increased risk for infections persisted after controlling for surgery duration (odds ratio, 1.3; 95% CI, 1.1–1.5). The majority of cases were spine surgeries, and resident involvement was not associated with morbidity or mortality for malignant tumor and aneurysm patients. Training level of residents was not associated with differences in outcomes. Conclusion Resident involvement was more common in sicker patients undergoing complex procedures, consistent with academic centers undertaking more complex cases. After controlling for patient and intraoperative characteristics, resident involvement in neurosurgical cases continued to be associated with longer surgical duration and slightly higher infection rates. Longer surgery duration did not account for differences in infection rates.